Multiple solutions of convection boundary layer flow for different types of fluids with various boundary conditions - Muhad Saleh, Siti Hidayah (2017)
In this study, similarity solutions of boundary layer flow and heat transfer in viscous fluid, micropolar fluid and nanofluid are considered for either mixed convection or magnetohydrodynamic (MHD)-forced convection. The objectives of the thesis are to analyse mathematical models of heat and mass transfer problems and to obtain the numerical results of each problem. The scope of this study is limited to two-dimensional or three-dimensional, steady or unsteady, incompressible, laminar boundary layer flows in viscous fluid, micropolar fluid or nanofluid. The first two problems are restricted to mixed convection effects while the rest are explored on forced convection. These problems are modeled to investigate and study their effects on a choice of fluids with various boundary conditions. The studies on stagnation point flow behavior have also been integrated including the non-aligned stagnation point. Besides, the effects of stretching/shrinking surface, permeable surface and also convective boundary condition have also been considered. Moreover, the consequence of moving wall also has been studied. The mathematical models for this problem are formulated, analyzed and simplified, and further transformed to non-dimensional form using non-dimensional variables. Next, the governing nonlinear partial differential equations are transformed to a system of ordinary differential equations using the similarity variables and are solved numerically using the shooting technique. Numerical results presented include the velocity, temperature, nanoparticle fraction (nanofluid) and angular velocity (micropolar fluid) profiles as well as the fluid flow and heat transfer characteristics for a range of the governing parameters. All the numerical solutions are presented in the form of tables and figures. Additionally, the existences of multiple solutions are contributed by the applied numerical method (shooting method) and the involvement of certain parameters in the system. The multiple solutions are reached for shrinking sheet case. Besides, it was also occur when mixed convection, suction and unsteadiness parameter added into the system of equations. The numerical results presented constitute an invaluable reference against which other exact or approximate solutions can be compared in the future.